Development of technology for extended-shelf-life meat products - L. Bal-Prylypko; O. Kanishchev; M. Mushtruk; B. Leonova (Тваринництво та технології харчових продуктів, 2024)
The development of new technologies to preserve the quality of meat products is of significant relevance in light of the growing global demand for safe, durable, and functional food products that meet modern healthy eating standards. This is particularly important given the challenges associated with ensuring global food security. This study aimed to design an innovative production technology for meat products that ensures an extended shelf life without compromising their organoleptic properties. The research employed contemporary methods of physicochemical and microbiological analysis, along with biotechnological approaches, particularly the use of starter cultures of lactic acid bacteria and bifidobacteria. The findings confirmed the positive influence of probiotic cultures on the biochemical processes occurring in meat raw materials. Specifically, these cultures facilitated fermentation, maturation, and the development of stable organoleptic characteristics. Furthermore, it was established that the use of probiotics reduced water activity and pH levels, thereby significantly enhancing the microbiological stability of meat products. The analysis of technological parameters, such as salting, maturation, and drying periods, demonstrated their critical role in shaping the flavour and aroma profiles, texture, and colour of the final product. As a result of this study, innovative production technology for meat products was developed, enabling the creation of items with high protein content, low fat content, and stable microbiological safety, with an extended shelf life of up to 45 days. The practical value of this research lies in the potential for wide-scale implementation of the developed innovative technology in the food industry for the production of high-quality dry-cured and fermented meat products. These products meet contemporary standards of safety and nutritional value. The use of probiotic cultures contributes to the creation of products with enhanced organoleptic properties and additional functional benefits, aligning with healthy eating trends and addressing consumer demand for natural and environmentally friendly products